Baroreflex sensitivity following acute upper-body exercise in the cold among stable coronary artery disease patients - Pikkarainen, Kalle; Valtonen, Rasmus I. P.; Hintsala, Heidi E.; Kiviniemi, Antti; Crandall, Craig G.; Perkiömäki, Juha; Hautala, Arto J.; Tulppo, Mikko P.; Jaakkola, Jouni J. K.; Ikäheimo, Tiina M. (Frontiers in Physiology, 2023)
Background. A cold environment and exercise separately affect the autonomic nervous system (ANS), baroreflex sensitivity (BRS), and blood pressure variability (BPV) but their combined effects on post-exercise recovery are not known. Our cross-over trial examined these responses following upper-body static and dynamic exercise performed in a cold and neutral environment in patients with coronary artery disease (CAD). Methods. 20 patients with stable CAD performed both graded static (10-30 % of maximal voluntary contraction) and dynamic (light, moderate and high perceived intensity) upper-body exercise at -15 °C and +22 °C for 30 min. Electrocardiogram and continuous blood pressure were measured to compute post-exercise (10 and 30 min after exercise) spectral powers of heart rate (HR), BPV and BRS at low (0.04-0.15 Hz) and high (0.15-0.4 Hz) frequencies. Results. Static upper-body exercise performed in a cold environment increased post-exercise high frequency (HF) spectral power of heart rate (HF RR) (p<0.001) and reduced HR (p=0.001) and lowto-high frequency (LF/HF) ratio (p=0.006) more than in a neutral environment. In addition, postexercise mean BRS (p=0.015) and HF BRS (p=0.041) increased more following static exercise in the cold than in a neutral environment. Dynamic upper-body exercise performed in a cold environment reduced post-exercise HF BRS (p=0.019) and systolic blood pressure (p=0.003). Conclusions. Static upper-body exercise in the cold increased post-exercise BRS and overall higher vagal activity but without reduced SBP. Dynamic upper-body exercise in the cold reduced post-exercise vagal BRS but did not affect the other parameters. The influence of cold exposure on post-exercise autonomic and cardiovascular responses following static upper-body exercise require further studies. This information helps understanding why persons with cardiovascular diseases are vulnerable to low environmental temperature.ClinicalTrials.gov: NCT02855905 (04/08/2016).